Desenvolvimento de um videocurso sobre o software de simulação LTspice - Silva, Gabriel Santos da (Universidade Federal de São Carlos, 2023)
This article describes the creation of an introductory video course on the LTspice circuit simulation software, with a focus on meeting the learning needs of students and electronics enthusiasts. The course comprises eleven videos covering topics from the initial download to advanced subjects, and emphasizes the significance of this educational resource for the Electrical Engineering community. Furthermore, it highlights the potential to establish a culture of video course creation as part of an extension activity.
Development of a video course on the LTspice simulation software
Keywords: Videocurso LTspice; Aprendizado; Engenharia Elétrica; LTspice video course; Learning; Electrical Engineering; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS